ANALISIS KONTEN PROGRAM “ARISAN” TRANS 7 SEBAGAI MEDIA HIBURAN DAN PENGETAHUAN - Alifahtinayah Adys Pradityawati; Makroen Sanjaya (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the content of the Arisan program on Trans7 as a medium that not only delivers entertainment but also contains educational elements. The program is a game show featuring quiz segments and interactive games with participants from various backgrounds. This research uses a qualitative method with Berelson’s content analysis approach and relates the findings to Harold Lasswell’s mass media function theory. The results show that Arisan Trans7 serves not only as entertainment through humorous hosting styles and comedic participant interactions but also subtly conveys knowledge through quiz questions covering topics such as history, culture, music, and general knowledge. The program also successfully represents the diversity of Indonesian society through its participant segmentation. In conclusion, Arisan Trans7 effectively balances the media's functions of entertainment and education through a light and enjoyable show format.